2010
DOI: 10.1177/1088767910371190
|View full text |Cite
|
Sign up to set email alerts
|

Latino Immigration, Economic Deprivation, and Violence: Regional Differences in the Effect of Linguistic Isolation

Abstract: One of the many contributions of Land, McCall, and Cohen’s landmark study was the confirmation of a long-held view in criminology—that deprivation raises homicide. Yet recent literature finds that although Latino immigrant communities are often poor, paradoxically they have low levels of crime. Unfortunately, this seemingly contradictory evidence is based on studies of long-established, well-organized, traditional immigrant communities where Spanish is a modal form of communication. However, recent Latino migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 62 publications
4
86
2
Order By: Relevance
“…Recent work by Shihadeh and Winters (2010) suggests that Latinos may be able to offset the lack of existing immigrant community by relying more on local religious ecology to keep crime low and community strong. This study also adds weight to previous findings of Shihadeh and Barranco (2010;, however, to suggest that high Latino immigration areas are not the safe havens they are in traditional destinations. Instead Latinos are murdered at an exceedingly high rate.…”
Section: New Destinationsmentioning
confidence: 54%
See 4 more Smart Citations
“…Recent work by Shihadeh and Winters (2010) suggests that Latinos may be able to offset the lack of existing immigrant community by relying more on local religious ecology to keep crime low and community strong. This study also adds weight to previous findings of Shihadeh and Barranco (2010;, however, to suggest that high Latino immigration areas are not the safe havens they are in traditional destinations. Instead Latinos are murdered at an exceedingly high rate.…”
Section: New Destinationsmentioning
confidence: 54%
“…Recent immigrants to new destinations are disproportionately young men from Mexico and Central America who come in search of work but typically have little education and often no proof of citizenship. Under such conditions, while evidence has shown that Latinos may be murdered at an exceedingly rate (Shihadeh and Barranco 2010), elevated rates of property crime would also be expected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations